Cell SoC balancing using a cascaded full bridge multilevel converter in battery energy storage systems - Chatzinikolaou, E; Rogers, D; Rogers, D (IEEE, 2016)
This paper presents a method for achieving individual electrochemical cell balancing by using a cascaded full bridge multilevel converter where a single electrochemical cell is connected to each converter module. As a result, balancing at cell level is possible without additional circuitry, making this topology ideal for long service life grid storage and applications using second-life cells where the cells are inherently poorly matched. In order to estimate the relative state of charge between cells, the control flexibility of the multilevel converter is used to remove each cell from the current path without interrupting the operation of the system. This process eliminates the effect of the internal cell resistance and fast transient electrochemical phenomena and therefore the measured voltage serves as a high quality ‘pseudo open circuit’ voltage measurement. The proposed balancing strategy is validated using a 25 level cascaded full bridge multilevel converter prototype for the individual balancing of twelve lithium polymer cells, during consecutive charging and discharging cycles. Successful balancing to within 5 mV of open circuit voltage is observed between cells with 45% difference in nominal capacity and 55% initial state of charge variation.